ASPEK BUDAYA DESAIN GRAFIS - Soeprapto Soedjono (Universitas Trisakti, 2006)
Abstract As a human creation, a grahic design is called cultural product due to its exixtence that has been created for fulfilling human's need by its capacity to share information through the cultural communication process. Its appearance that loaded with sense of techniques, ethics, and aesthetics values, a graphic design not jus functioning only as a visula 'message carrier' but it has been created in a form of cerative-aesthetics to serve its high-end objectives.Whilst its embedded cultural values lies not just in the viusal appearence alone but also in variety of considerations pertaining its formal elements and the meaning of its contents as well.Included within are any creative objectives wirh historical, communicative, aesthetics, economic, social politics and psychological values AbstrakSebagai karya cipta manusia desain grafis dikatakan sebagai produk budaya karena sifat entitasnya yang diciptakan bagi pemenuhan kebutuhan manusia dalam kelompoknya yang slaing berbagi informasi melalui proses komunikasi budaya. Dalam penampilannya yang sarat dengan nuansa teknik, etika dan estetika, desain grafis tidak sekedar berfungsi sebagai 'message carrier' semata tetapi merupakan bentuk medium yang dikemas secara estetis-kretaif guna memenuhi tujuan akhir penampilannya.Sedangkan nilai budaya yang dikandungnya tidak sekedar tercermin dalam tampilan wujud visualnya saja tetapi juga dalam beragam perimbangan penciptaan unsur-unsur bentuk dan mkana pesan yang dikandungnya. termasuk di dalamnya adalah varians tujuan penciptaaan desain grafis yang memiliki nilai historis , komunikatif estetis, ekonomis , sosial, politis dan psikologis.